Kekuatan Hukum Pembuktian Akta Di bawah Tangan Yang Dilegalisasi Oleh Pejabat Berwenang - Berliana, Ade; Hamza, Yuli Adha; Rezky Wulandari, Andi Sri (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This study aims to find out and analyze the legal position of legalized private deeds, find out and analyze the strength of proof of legalized illegal deeds as evidence in civil cases. This type of research uses empirical research methods. The results of this study indicate that Article 1338 of the Civil Code which states that